Patient Safety Education 20 Years After the Institute of Medicine Report: Results From a Cross-sectional National Survey. Issue 8 (December 2021) - Arora, Sonal; Tsang, Fiona; Kekecs, Zoltan; Shah, Nisha; Archer, Stephanie; Smith, Jason; Darzi, Ara
Abstract : Objectives: Educating healthcare professionals in patient safety is essential to achieving sustainable improvements in care. This study aimed to identify the key constituents of patient safety education alongside its facilitators and barriers from a frontline perspective. Methods: An electronic survey was sent to 592 healthcare professionals and educators in patient safety education in the United Kingdom. Two independent reviewers conducted a thematic analysis of the free-text data. Themes focused on effective content, learning practices and facilitators and barriers to patient safety education. Results: Of 592 individuals completing the survey, 545 (92%) submitted analyzable responses. Interrater reliability of coding was high with Cohen k value of 0.86. Participants endorsed experiential and interactive learning as ideal modalities for delivery and expressed a need for content to be based on real clinical cases and tailored to the needs of the learners. The most commonly mentioned facilitators were standardization of methods and assessment (49%), dedicated funding (21%), and culture of openness (20%). Staffing problems and high workload (41%) and lack of accessibility of training (23%) were identified as primary barriers of efficacy and uptake. Conclusions: This study identified key factors to the success of patient safety education in terms of content and delivery alongside facilitators and barriers. Future curricula developers and interventions should improve standardization, funding, culture, and access so as to optimize education programs to enhance patient safety.